Excellent synergy of formability and strength of a Mg-Zn-Y-Ca-Zr alloy by tailoring segregation-assisted weak elliptical ring texture - Ming Yang; Hai-Long Jia; Run Jiang; Xiao-Li Zhou; Pin-Kui Ma; Zhi-Gang Li; Min Zha; Hui-Yuan Wang (Journal of Magnesium and Alloys)
In this work, a good balance of strength and ductility (a yield strength of ∼185 MPa and a uniform elongation of ∼20%) has been obtained in a dilute Mg-1.8Zn-0.3Y-0.3Ca-0.3Zr (wt.%) alloy using hard plate rolling (HPR) followed by annealing, with a low anisotropy in mechanical properties. More importantly, the HPR-annealed alloy shows an excellent formability at the same time, i.e., the index Erichsen (I.E.) value reaches ∼7.9 mm (the Erichsen cupping test) at room temperature, which is higher compared with the Mg-1.8Zn-0.3Y-0.3Ca-0.3Zr alloy produced by conventional multi-pass rolling (CR) followed by annealing. The excellent synergy of strength and formability of the HPR-annealed alloy is mainly attributed to a weak elliptical ring texture, as well as finer and denser Zn2Zr3 precipitates. The formation of weak elliptical ring texture is related to the preferential co-segregation of Zn and Ca elements at boundaries of basal grains with small misorientation angles during annealing, which inhibits the growth of basal grains and promotes the preferential growth of non-basal grains. At the same time, in comparison with the CR-annealed alloy, the HPR-annealed alloy contains finer and denser Zn2Zr3 precipitates that are less likely to become sources of cracks, leading to the higher strength and formability of the HPR-annealed alloy. The results in this work can provide reference for the development of high strength Mg alloy sheets with excellent room temperature formability, which also shed light on mitigating planar anisotropy in mechanical properties for Mg alloy sheets.